Reasons for extraction of deciduous teeth in school children aged 5-12 years at Baiturrahmah Dental Hospital - Sri P. Utami; Bunga R. Audilla (Journal of Dentomaxillofacial Science, 2021)
Objective: Humans have 2 types of teeth namely deciduous and permanent teeth, so these are known as diphodonts. Primary teeth or also known as deciduous teeth or milk teeth count as many as 20 teeth (10 teeth in each arch). Material and Methods: a dental health program in children aged 5 to 12 years. A total of 30 samples at Baiturrahmah University Dental Hospital, children were randomly selected in this study. Age criteria must be met according to the study. Children who had a 5th birthday were included in the 5-year age group and then the same in the rest of the age group. Results: This study found that the extracted teeth also experienced persistence (55%). The reason the patient did not extract the tooth so that it experienced persistence was because the patient was afraid to come to the dentist for extraction. Conclusion: In this study, persistent teeth were the main trigger that could cause dental malocclusion. Crowded teeth are defined as the difference in the relationship between tooth size and jaw size, causing the teeth to overlap. In other literature crowding is described as an unequal proportion of the tooth to the surrounding tissue. 4 Crowded teeth can be located lingually or palatally, labial or buccally, or can rotate on their axis. The prevalence of crowding teeth is more than the prevalence of other macocclusions such as spacing, open bite, deep bite, crossbite.